1979
DOI: 10.1152/jappl.1979.47.2.453
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of positive-pressure ventilation in normal subjects

Abstract: In normal subjects during 15-min positive-pressure ventilation with 10 cmH2O end-expiratory pressure (PEEP), cardiac output fell 19% due to a fall in stroke volume. Transmural mean right atrial pressure rose 3.1 cmH2O and right ventricular end-diastolic diameter increased 15%. Simultaneously, left ventricular end-diastolic diameter decreased 21%, ejection time increased 11%, and velocity of circumferential fiber shortening fell 30%. Thus, right ventricular filling increased and left ventricular filling decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(20 citation statements)
references
References 0 publications
1
17
1
1
Order By: Relevance
“…Others have noted an increase in the amount of lung water with PEEP under certain specific experimental conditions (1,6,15). Our findings regarding rebreathing measurements of VTPC in piglets in this study as well as in dogs in a previous study from our laboratory (12) does differ from the study by Cassidy et al (3), who reported an increase in rebreathing VTPC in humans with the application of 10 cm H 2 0 PEEP. We cannot explain the difference between these studies.…”
Section: Discussioncontrasting
confidence: 92%
“…Others have noted an increase in the amount of lung water with PEEP under certain specific experimental conditions (1,6,15). Our findings regarding rebreathing measurements of VTPC in piglets in this study as well as in dogs in a previous study from our laboratory (12) does differ from the study by Cassidy et al (3), who reported an increase in rebreathing VTPC in humans with the application of 10 cm H 2 0 PEEP. We cannot explain the difference between these studies.…”
Section: Discussioncontrasting
confidence: 92%
“…PEEP generally decreases cardiac output, and the cause of this decrease has been the focus of much research over the past decade. A few studies in intact animals or humans have suggested impairment of cardiac contractility on PEEP [48,50]. MANNY et al [51] perfused an isolated heart with blood from a support dog.…”
Section: Steady-state Effects Positive End-expiratory Pressure and Comentioning
confidence: 99%
“…This technique has already been shown to be accurate and reproducible in animal studies of lung injury (6) and in adult human studies (7). Recently, we have shown that this technique provides an accurate measurement of cardiopulmonary function in mechanically ventilated piglets, comparable in size to the human neonate, including piglets with oleic-acid induced lung injury ventilated using PEEP (8).…”
mentioning
confidence: 93%